Analysis of Thermal Comfort in Green Open Spaces (GOS) Using the Temperature Humidity Index (THI) Approach (Case Study: City Park Green Open Space in Lhokseumawe) - Indri Nuraini; Adi Safyan; Yenny Novianti (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The city of Lhokseumawe, located in a coastal area with a tropical monsoon climate, faces challenges in creating comfort due to high solar radiation and air temperatures. The Green Open Spaces (GOS) in this city, such as Riyadhah Park, Hiraq Field, and General Sudirman Field, are often utilized for various activities like walking, recreation, sports, eating, drinking, commercial activities, ceremonies, and playing. Public comfort, particularly in city parks, should be prioritized to create an ideal environment. This study aims to analyze thermal comfort using the Temperature Humidity Index (THI) approach. The research was conducted from May 27 to June 10, 2024, during a period when temperatures in Indonesia increased due to the apparent movement of the sun. The method used is quantitative descriptive research. Based on measurements taken over 15 days at three different intervals, the morning THI in the three study locations, namely Riyadhah Park, Hiraq Field, and General Sudirman Field, indicated that shaded areas with vegetation had slightly lower THI values compared to unshaded areas. The average THI for shaded areas ranged from 29,3°C to 29,7°C, while unshaded areas ranged from 29,7°C to 30°C. All areas in the morning were classified as moderately comfortable. At midday, the THI difference between shaded and unshaded areas was more pronounced. THI in shaded areas at Riyadhah Park, Hiraq Field, and General Sudirman Field ranged from 31,9°C to 32,2°C, while unshaded areas had higher values, between 32,4°C and 32,6°C. All areas at the three locations during midday fell into the uncomfortable category. Measurements taken in the afternoon showed a pattern similar to midday, where shaded areas had slightly lower THI values than unshaded areas. The average THI for shaded areas ranged from 30,7°C to 30,9°C, while unshaded areas ranged from 31,1°C to 31,3°C. All areas at the three locations in the afternoon were classified as uncomfortable. Overall, shaded areas in the three study locations consistently showed lower THI values compared to unshaded areas, indicating that the presence of vegetation can help reduce temperatures and enhance thermal comfort, especially during times of higher heat intensity, such as midday and afternoon.